A framework for integrating scientific forecasts with indigenous systems of weather forecasting in southern Nigeria. Issue 4 (18th May 2020) - Ebhuoma, Eromose E.
ABSTRACT: In Delta state, Nigeria, where food production is rain-fed, climatic risks have compromised rural livelihoods. Information about future weather conditions can help farmers adapt more efficiently. Data obtained using group discussions and semi-structured interviews revealed that farmers in Delta state rely on indigenous knowledge systems, despite occasional inconsistencies. Most farmers' trust in seasonal climate forecasts has dwindled because they suffered losses when previously relying on the seasonal forecasts in a planting season. With climatic risks expected to increase by 2030, there is a need to rebuild farmers' trust in seasonal climate forecasts, using a proposed multiple evidence-based approach.